Waitress Efforts to Increase Sales at Sundara Restaurant Four Seasons Resort Bali at Jimbaran Bay - Satia Negara, I Made Weda; Agus Selamet, I Wayan; Wichitakani Wahyu C, Putu Bagus; Wirawan, I Wayan (Akademi Komunitas MAPINDO, 2023)
This study discusses the efforts of waiters to increase sales at Sundara Restaurant- Four Seasons Resort Bali At Jimbaran Bay. Taking the problem of sales at the restaurant has decreased. In this study using a qualitative descriptive method. Collecting data using interviews, observation, documentation and literature. The sample in this study was taken purposively. The data were analyzed using qualitative analysis using four stages which included: Data Collection, Data Reduction, Data Presentation, Drawing Conclusions. The results of the study show that in increasing sales, waiters carry out various efforts, including: improving service to customers in terms of appearance, reliability, responsiveness, assurance, waiters doing upselling, waiters doing promotions. Obstacles in sales from the results of the study show that the characters of guests or customers differ in terms of their purchases, lack of menu knowledge (Product Knowledge) and constraints in the customer's holiday season. Keywords: Waitressing, Sales, and Barriers